The Impact of Older Age and Sex on Motion Discrimination. Issue 1 (1st January 2017) - Conlon, Elizabeth G.; Power, Garry F.; Hine, Trevor J.; Rahaley, Nicole
Abstract : Background/Study Context: Reports of age-related differences on motion discrimination tasks have produced inconsistent findings concerning the influence of sex. Some studies have reported that older women have higher thresholds than older men, with others finding that women have higher motion thresholds regardless of age group. Reports of the age at which declines in motion discrimination first occur also differ, with some studies reporting declines only in groups aged over 70 years, with others reporting that age-related decline occurs at a younger age. The current study aimed to determine whether the sex differences found occur because relative to men, women have greater difficulty extracting motion signals from noise (Experiment 1) or have greater difficulty making use of the available motion cues (Experiment 2) in these complex moving stimuli. In addition, the influence of these manipulations on groups aged under and over 70 years was explored . Methods: Motion discrimination measures were obtained using 39 older adults aged between 60 and 85 years (21 women) and 40 younger adults aged between 20 and 45 years (20 women). In Experiment 1, coherent motion and relative motion displacement thresholds were obtained. In Experiment 2, coherent motion thresholds were obtained for stimuli containing either 150 or 600 dots . Results: In Experiment 1, the older group had significantly higher thresholds on the relative motion displacement and coherent motion tasks than a younger group. No differences in motion sensitivity were found in the older groups aged under or over 70 years. Women regardless of age group had significantly higher thresholds than men on both tasks. In Experiment 2, the older group had higher coherence thresholds than the younger group, and the number of dots presented had no influence on thresholds, for the older group or older women specifically. In the younger group, women had higher coherence thresholds than men with presentation of 150 but not 600 dots. There were 51% of the older group who showed evidence of age-related decline on all the motion coherence tasks conducted, with half of these in each the group aged under and over 70 years . Conclusion: Difficulties with noise exclusion failed to explain the sex differences found. The increased number of motion cues present when a larger number of dots were included was sufficient to reduce coherence thresholds in younger women but not older men or women. In addition to age, developmental history and sex may provide further predictors in older individuals of decline on measures of motion discrimination.